Non-state Actors in the International Climate Change Regulatory Framework - Bergmann, Sina (Helsinki Law Review, 2021)
Global climate governance is multilateral and involves both state and non-state actors. This study sets to identify the ways in which non-state actors can access and participate in the international climate change regime under the UNFCCC and the 2015 Paris Agreement and to evaluate how they can influence law-making processes and outcomes under the agreements. The study further provides recommendations on how the involvement of non-state actors can be improved under the agreements. The study emphasizes that under the UNFCCC, non-state actors have an important role in acting as intermediaries under the orchestration governance model and in participating to the Conference of Parties and under the Paris Agreement, by exerting influence on state’s nationally determined contributions. The study suggests that the role of non-state actors in formulating nationally determined contributions and in participating to the Conference of Parties should be further formalised and that the NAZCA portal should be improved.